Strategi Bimbingan Kelompok dalam Mereduksi Kecemasan Berbicara di Depan Umum (Glossophobia) pada Siswa SMA Swasta Imelda Medan - Suci Ramadani; Uli Makmun Hasibuan; Dini Fidianti; Nurhalimah Nurhalimah (Kampus Akademik Publiser, 2026)
Bullying in junior high school (SMP) environments is a serious problem that negatively impacts students' psychological, academic, and social development. Guidance and Counseling (BK) teachers hold a strategic role in preventing and handling bullying behavior in school settings. This article aims to examine in depth the role of BK teachers in addressing various forms of bullying in junior high schools through a literature review approach. Research data was obtained from various Indonesian-language scientific journals published after 2021. The results show that BK teachers play a role through various services, including information services, individual counseling, group guidance, group counseling, mediation, and collaboration with parents and school staff. The effectiveness of the BK teacher's role is greatly influenced by supporting factors such as firm school policies, an ideal BK teacher-student ratio, and active parental involvement. This research is expected to serve as a reference for BK practitioners in designing more comprehensive and sustainable bullying intervention programs.